Mechanical properties of composite board prepared by using high density polyethylene (HDPE) and saw dust with addition of Maleic Anyhride (MA) as coupling agent: article - Roshaizi, Nurul Aliad; Mulana, Farid (2019)
Increasing amount of agriculture waste in Malaysia recent years has brought many environmental issues and economic concerns in the country. This study presents the excessive wood sawdust was recycled and used as organic filler and high density polyethylene (HDPE) as polymer matrix in produces the sample of composite board with the addition of maleic anyhride (MA) as coupling agent. Fillers and matrix were weight according to the percent formulation of 20:70, 30:60, 40:50 and 50:40 respectively. Though, the amount of coupling agent added was fixed to 10% of total weight of every sample. The composites were prepared by using hot press which needs to produce different molding for every mechanical properties and small amount of each sample were taken and their mechanical properties for flexural and tensile strength were studied. In conclusion, both flexural strength and tensile strength were found to improve with addition of coupling agent in composites which was related to improved interfacial bonding between the natural fibers as filler and the HDPE as a polymer matrix.